Seguimiento farmacoterapéutico a pacientes con hipertensión arterial del albergue central “Ignacia Rodulfo Viuda de Canevaro” - Juárez, José R. (2019)
The objective of this research was to provide a pharmacotherapeutic follow-up service (SFT) for elderly adults diagnosed with arterial hypertension, residents in a shelter for the elderly; as well as identifying the causes and factors associated with Problems Related to Medicines (PRM), contributing to improve blood pressure levels. It is a descriptive, prospective and longitudinal study over a period of six months, with 22 patients who met the selection criteria with an average age of 82 years, of which 70% were women. The review of the clinical history, interviews with each patient; identifying that the majori-ty had three diagnoses (Among others: hypertension, gastritis, osteoarthritis, osteoporosis, hypercholesterolemia, pain and other diseases); 30% had three medications prescribed and only 5% had completed higher education; Likewise, values of systolic blood pressure of 130 mmHg (p <0.001) and diastolic blood pressure of 80 mmHg were obtained (p <0.005). Using the DADER methodology tools, the SFT cards were analyzed. Only the study concluded 20 of the 22 patients who started the study. During the study period, 48 PRMs were identified, with PRM 1 (44%) being the most frequent, followed by PRM 5 (25%). The most frequent causes were noncompliance (17%) and probability of adverse effects (15%); associated factors were identified: number of diagnoses and medications and level of education.